2014
DOI: 10.1039/c4nr02239d
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Mn-doped I–III–VI quantum dots for near infrared fluorescence and magnetic resonance imaging: from synthesis to in vivo application

Abstract: The development of sensitive multimodal contrast agents is a key issue to provide better global, multi-scale images for diagnostic or therapeutic purposes. Here we present the synthesis of Zn-Cu-In-(S, Se)/Zn(1-x)Mn(x)S core-shell quantum dots (QDs) that can be used as markers for both near-infrared fluorescence imaging and magnetic resonance imaging (MRI). We first present the synthesis of Zn-Cu-In-(S, Se) cores coated with a thick ZnS shell doped with various proportions of Mn. Their emission wavelengths can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 51 publications
0
44
0
Order By: Relevance
“…35 Figure 2b shows the calculated r 1p(particle) of each SMNP. Interestingly, the plots of r 1p(particle) and r 1p(Fe(III)) show different trends ( i.e ., see Figure S5 for r 1p(particle) and r 1p(Fe(III)) results of SMNPs at 20 MHz).…”
Section: Resultsmentioning
confidence: 99%
“…35 Figure 2b shows the calculated r 1p(particle) of each SMNP. Interestingly, the plots of r 1p(particle) and r 1p(Fe(III)) show different trends ( i.e ., see Figure S5 for r 1p(particle) and r 1p(Fe(III)) results of SMNPs at 20 MHz).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, their bandgaps can be tailored widely by growing a ZnS shell or making them be alloyed CuZnInS (CZIS) NCs with Zn, to meet the prerequisite for the well-resolved Mn 2+ d-d emission, which can be expected to be the ideal “green” materials for widespread technological applications where the Mn 2+ emission required171819. As compared to the CZIS alloyed QDs, the CIS-ZnS core-shell counterparts with the designed growth of ZnS shells, show the remarkable advantages to offer a significantly effective surface passivation for higher PL QYs192021222324, as well a more facility to control the Mn 2+ positions25. For examples, Yang et al reported the synthesis of Mn 2+ -doped CdS/ZnS core-shell NCs with Mn 2+ at controlled radial positions used a three-step synthesis route25.…”
mentioning
confidence: 99%
“…The same strategy has been used with quantum dots, mainly by incorporating Mn 2+ ions to produce bimodal MR/fluorescent probes. For example, Sitbon et al have shown that Zn-Cu-In-Se/Zn 0.9 Mn 0.1 S QDs can be used to detect regional lymph nodes in both MRI and NIR fluorescence imaging ( Figure 4) [60]. More recently, the incorporation of 64 Cu by cation exchange enables their use as PET/fluorescence contrast agents [61].…”
Section: Multimodal Imagingmentioning
confidence: 97%
“…T1-weighted MRI images of a mouse before (a) and after (b) injection of QDs and the corresponding NIR fluorescence image (c). (Reproduced from ref [60]. with permission from the Royal Society of Chemistry).…”
mentioning
confidence: 99%